Implementation of Lecturer Learner Leadership In the Formation of Student Learning Behavior at World Class Universities - Aedi , Nur (Journal of Ecohumanism, 2024)
This research explains new issues about the leadership of lecturer-learners in shaping student learning behavior in world-class universities. This study uses quantitative methods with variables of lecturer learner leadership and student learning behavior at world-class universities. The population in this study consisted of 41 world-class universities with 501 lecturer respondents and 708 student respondents with the total number of respondents who filled out questionaires totaling 1209 respondents. The results of this study provide an explanation that the implementation of lecturer learner leadership has a significant and high impact on the formation of student learning behavior, meaning that the higher the learner leadership implemented by lecturers, there will be an increased positive impact on the formation of student learning behavior. The recommendation of this study is that world-class universities must work harder in supporting learner-leadership values for lecturers, especially in providing educational services for students because the behavior of lecturer-learners is reflected in the formation of the beahavior of student learning.